HUBUNGAN DAYA LEDAK OTOT LENGAN DAN BAHU DENGAN KEMAMPUAN PUKULAN LOB ATLET BULUTANGKIS CLUB GEMPARS FC BHAYANGKARA BAGAN SIAPI-API KABUPATEN ROKAN HILIR - Habibi '; Saripin '; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
ABSTRACT, Background problem in this research is the lob badminton ability not optimal yet of being owned Gempars FC athletes. This problem can be seen from the observation of researchers during a match or training, it is suspected because of the explosive power arms and shoulders muscle. Therefore, the purpose of this study was to determine whether there is a corelation explosive power arms and shoulders muscle with lob badminton ablitiy Gempars FC athletes. This type of research is correlational comparing the measurement results of two different variables in order to determine the degree of correlation between these variables. As independent variables (X1) is the explosive power arms and shoulders muscles, while the dependent variable (Y) is lob badminton ability. This research data obtained from two hand medicine ball put test, and lob badminton ability test. Based on the research results can be concluded as follows: There is a significant corelation between the explosive power arm and shoulders muscles (X1) to lob badminton ability (Y) Club Gempars Bhayangkara Siapi Bagan Api, obtained rhitung = 0,579> rtabel = 0.361.Keywords : Explosive Power, Arms and Shoulder, Lob, Badminton